Studi Literatur Potensi Ekstrak Zat Warna Alam sebagai Indikator Asam Basa Alternatif - Alifa Gunawan Yusuf; Naila Najiyah; Edi Wahyu Sri Mulyono; Fauzi Abdilah (Jurnal Kimia Fullerene, 2021)
Currently, the use of acid-base indicators is limited to synthetic indicators, which are relatively expensive and not environmentally friendly. Therefore, an alternative acid-base indicator is needed from natural ingredients containing anthocyanins which are relatively cheaper, easy to obtain, and environmentally friendly so that they can replace the function of synthetic indicators. For this reason, it is necessary to research beforehand on the sources of raw materials that can be used as alternative acid-base indicators, how the method and what solvents are suitable, as well as the character of the anthocyanin dye extract obtained. In this research, a literature study related to the potential of natural dye extracts was carried out as an alternative acid-base indicator. From the results of the literature study, it can be seen that natural ingredients derived from groups of vegetables, flowers, fruits, and tubers have the potential as raw materials for making alternative acid-base indicators. The best method for extracting anthocyanin dyes from natural materials is the maceration method and the solvent that is suitable for use is ethanol-HCl solvent. The results of titration using natural dye extract indicators have similarities with the results of titrations using phenolphthalein and methyl orange indicators so that natural dye extract indicators can be used as alternative indicators in acid-base titrations.